Rancang Bangun Sistem Informasi Objek Wisata Hiu Paus Teluk Saleh Berbasis Web dengan Metode Agile - Dinan Yulianto; Firda Mardiaturrahman (Jurnal Media Computer Science, 2026)
Whale shark tourism in Saleh Bay, Sumbawa Regency, as a prominent marine tourism destination, provides interactive experiences between tourists and whale sharks; however, interviews, questionnaires, and field observations reveal several challenges, including suboptimal digital promotion, the absence of an integrated reservation system, and manual administrative data management, leading to data duplication, potential data loss, and difficulties in performance reporting. This study aims to develop and evaluate a web-based information system that integrates promotional features, a unified reservation system, a statistical reporting dashboard, and social media integration. The system development follows the Agile methodology within a software development life cycle framework, including requirement analysis, system design, implementation, functional testing, deployment, and usability evaluation, and was completed over five sprints within fifteen weeks. Functional testing using black-box testing confirms that all system components operate as intended. Furthermore, usability evaluation using the User Experience Questionnaire (UEQ), involving 35 respondents comprising tourism managers and visitors, indicates mean scores for attractiveness (1.11), perspicuity (1.32), efficiency (1.26), dependability (0.93), and stimulation (0.85), all reflecting positive impressions (>0.80), while novelty (0.60) indicates a neutral impression.